(untitled) (Tempo e Argumento, 2022)
The article’s aim is to study and analyze the political messages of a set of caricatures published by five newspapers of the Brazilian mainstream press (Correio da Manhã, Folha de S. Paulo, Jornal do Brasil, O Estado de S. Paulo and Última Hora) dedicated to the bipartisan system in force during the first years of the military dictatorship (1966-1979). The purpose is to analyze the different ways in which the caricatures represented the parties to their public, considering the changes that occurred over time and the different positions of the cartoonists and their journalistic companies in face of the political project of the dictatorial regime.